PENGARUH PENGGUNAAN GADGET TERHADAP PENURUNAN KETAJAMAN PENGLIHATAN PADA REMAJA TAHUN 2020 - Qonita Qonita; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2021)
Based on a survey that has been done the increase in children who have used glasses has reached 10%, especially students in the City of South Tangerang. Last year the children who used glasses were caused by the factor of too often using smartphones reaching 24% but now it has reached 10%. Visual acuity disorders in school-age children are important health problems. Early detection and publication of the prevalence and factors associated with visual impairment in primary school students in Indonesia is still very rarely done. Methods: Researchers used data bases such as Google Scholar, Pubmed, and Pro-quest to search for articles by authors conducting searches in Indonesian and English with the keywords "gadget" "sharpness of vision / sharpness of vision" and "teenager / teenager", for look for journal articles covering keywords for the period 2015-2020. Results: Of the 27 articles found among them showed the results that there is a relationship between the use of gadgets with decreased visual acuity in teens. Discussion: Based on the results of interviews and observations obtained by the researchers, it is argued that there may be a number of things that affect the child's visual acuity, for example the position of the use of gadgets, lighting intensity, age and genetics. Conclusion: Based on the results of a literature review study obtained by researchers, it can be concluded that abnormalities in eye vision value are caused by playing bad gadgets, playing bad gadgets raises the risk of tired eyes. Eye disorders in children due to gadgets are increasing. Suggestion: This study shows that counseling about eye health is needed and factors that can affect the level of eye acuity in adolescents as a preventive measure.